2019
DOI: 10.1177/2320206819861223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Endocrowns on Fracture Strength and Microleakage of Endodontically Treated Primary Molar Teeth

Abstract: Objectives: Optimal restoration of endodontically treated teeth is very important for the durability of the endodontic treatment. The focus of this study was to evaluate the fracture strength and microleakage of composite endocrowns compared with Class II composite restorations in endodontically treated primary molar teeth. Materials and Methods: 48 extracted second primary molars were divided into 2 groups. Group 1 (control): teeth with Class II and endodontic access cavities restored with G-aenial composite;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…With regards to the flattening of the pulp chamber floor, previous studies reported different filling materials, such as: resin cement [ 18 ], flowable composite resin [ 19 ], moldable composite resin [ 20 ], and glass ionomer cement [ 21 ]. However, the reason to choose the filling material used to flatten the pulp chamber restoration has never been justified before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to the flattening of the pulp chamber floor, previous studies reported different filling materials, such as: resin cement [ 18 ], flowable composite resin [ 19 ], moldable composite resin [ 20 ], and glass ionomer cement [ 21 ]. However, the reason to choose the filling material used to flatten the pulp chamber restoration has never been justified before.…”
Section: Discussionmentioning
confidence: 99%
“…When the pulp chamber floor is not completely flattened, the incidence of unfavorable failures can increase [ 17 ], and the preparation impression and the endocrown design can be compromised [ 14 ]. There are reports of different filling materials applied to seal the root canal and to flatten the pulp chamber, such as: resin cement [ 18 ], flowable composite resin [ 18 , 19 ], sculptable composite resin [ 20 ], and glass ionomer cement [ 21 ]. However, there is no study in the literature that has evaluated the effect of different biomaterials to flatten the pulp chamber and to support the endocrown restoration.…”
Section: Introductionmentioning
confidence: 99%
“…Endocrowns have been widely used in the past few years [14] as they can offer a more conservative alternative restoration with accepted esthetics [1,19]. They consisted of two parts: a core and a crown acting as one piece where the macro retention is obtained from the pulp chamber and the micro retention is obtained from the adhesive resin cement [14,20].…”
Section: Discussionmentioning
confidence: 99%
“…Resin endocrown restorations provide more advantages being more economic treatment option as well as reduced preparation time, together with esthetic properties comparable to ceramics [21]. performance of endocrown and emphasized in their conclusion its success as restoration for endodontically treated permanent molars [14,22,23]. In the current in-vitro study, natural deciduous molars were utilized to nearly simulate the clinical condition in terms of the pulp chamber size, root canals contouring and the crown root ratio [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation